2012
DOI: 10.2174/138920012798918408
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Hydration of the Active Sites of Mammalian Cytochromes P450 Probed by Molecular Dynamics Simulations

Abstract: The flexibility, active site volume, solvation, and access path dynamics of six metabolically active mammalian cytochromes P450 (human 2A6, 2C9, 2D6, 2E1, 3A4 and rabbit 2B4) are extensively studied using molecular dynamics (MD) simulations. On average, the enzymes' overall structures equilibrate on a 50+ ns timescale. The very open CYP2B4 structure closes slowly over the course of the simulation. The volumes of the active sites fluctuate by more than 50% during the MD runs; these fluctuations are mainly due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 94 publications
6
47
0
Order By: Relevance
“…The frequencies of amino acids in the middle regions of the channels correspond to the frequencies in the entire channel with the exception of glycine (Gly) and aromatic amino acids (Trp, Tyr, Phe), which are present more frequently. We may hypothesize that the higher frequency of glycine (Gly) in the middle channel parts is because it facilitates flexibility, which may be important for substrate/product channeling between the active site and protein surface [29], whereas aromatic amino acids can serve as gate-keepers. External parts of the channel bear more charged residues than any other part (Arg, Lys, Glu, Asp) together with proline (Pro) and glutamine (Gln), whereas other polar residues (Ser, Thr) are surprisingly less common in the external parts even though that both Ser and Thr are evenly distributed within the structure of proteins (Additional file 1: Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequencies of amino acids in the middle regions of the channels correspond to the frequencies in the entire channel with the exception of glycine (Gly) and aromatic amino acids (Trp, Tyr, Phe), which are present more frequently. We may hypothesize that the higher frequency of glycine (Gly) in the middle channel parts is because it facilitates flexibility, which may be important for substrate/product channeling between the active site and protein surface [29], whereas aromatic amino acids can serve as gate-keepers. External parts of the channel bear more charged residues than any other part (Arg, Lys, Glu, Asp) together with proline (Pro) and glutamine (Gln), whereas other polar residues (Ser, Thr) are surprisingly less common in the external parts even though that both Ser and Thr are evenly distributed within the structure of proteins (Additional file 1: Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…The amino acids lining the access channels of cytochrome P450 (CYP) are important for the selectivity of these enzymes [28] while the flexibility of these channels, i.e. their opening and closing motions, contributes to the broad substrate specificity of CYP [10,29]. …”
Section: Introductionmentioning
confidence: 99%
“…First, active site water molecules were absent in the X-ray crystal structures of CYP2E1 with either 4-methylpyrazole or indazole [26], which was reasonable given the well-characterized hydrophobicity of the CYP2E1 access channel and active site. Second, previous MD simulations on the hydration of P450 active sites demonstrated that the access channel for CYP2E1 was often less than the diameter of a water molecule [27]. This restriction on movement of water and inherent hydrophobicity of the CYP2E1 active site and access channel would minimize the possibility of hydration within the enzyme.…”
Section: Methodsmentioning
confidence: 99%
“…macrolide antibiotics and steroids) (ref. [34][35][36][37] ). We reported earlier 38 that oxaliplatin exhibits only negligible effect on P450s even at very high concentration.…”
Section: Determination Of Cyp Activitiesmentioning
confidence: 99%